Associations between socioeconomic resources and adiposity traits in adults: Evidence from Samoa. (April 2020) - Choy, Courtney C.; Hawley, Nicola L.; Naseri, Take; Reupena, Muagututi'a Sefuiva; McGarvey, Stephen T.
Abstract: In low- and middle-income countries, earlier in economic development, obesity tends to be more prevalent in high socioeconomic resource groups compared to low. Later in development, the distribution of obesity tends to show the opposite pattern, becoming more prevalent in those with low socioeconomic resources. This shift in obesity prevalence tends to occur between a gross national income per capita (GNI) of US1, 000 to 4, 000 dollars. Whether a similar pattern occurs in Pacific Island countries has not been well documented. In Samoa, the GNI rose to US3, 200 dollars in 2010 at which time over 80% of adults were overweight or obese. We aimed to understand the association of socioeconomic resources, assessed by household assets, with adult body mass index (BMI) and abdominal circumference (AC) in Samoa. Data were from a genome-wide association study for obesity among 3, 370 Samoans aged 24.5-<65 years in 2010. Household asset scores were calculated based on ownership of consumer durables, housing construction, and access to basic services. Sex-stratified multivariate linear regressions were used to assess adiposity trait differences by household asset ownership, after controlling for age, education, and household urbanicity. Higher asset ownership was associated with higher BMI and AC and the positive relationship remained robust after controlling for potential confounders. Despite significant economic growth preceding the year 2010 in Samoa, the obesity burden had not shifted to low socioeconomic groups in a similar way that has been observed in countries further along in the economic transition. The mechanism by which socioeconomic resources influence adiposity is complex and may be particularly complicated in Samoa by migrant remittances received both as cash and household assets. Social and physical environments may constrain the positive health behavior change necessary to reduce obesity even in the context of high socioeconomic position, a situation that requires further investigation. Highlights: Despite economic growth in Samoa, obesity still impacts higher socioeconomic groups. Ownership of household assets was positively associated with adiposity traits. Associations remain in both females and males after accounting for confounders. Migrant remittances and environmental constraints may complicate the associations.